2008
DOI: 10.1177/156482650802900401
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin B12 Status of Pregnant Indian Women and Cognitive Function in their 9-year-old Children

Abstract: Maternal vitamin B12 status in pregnancy influences cognitive function in offspring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
125
4
4

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 124 publications
(139 citation statements)
references
References 27 publications
(27 reference statements)
5
125
4
4
Order By: Relevance
“…Two studies from India noted that a higher maternal vitamin B-12 status during pregnancy was associated with improved child cognitive outcomes and developmental indexes (43,45). One study from Mexico reported that inadequate maternal dietary intake of vitamin B-12 during pregnancy was associated with poorer developmental outcomes in their infants (50).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Two studies from India noted that a higher maternal vitamin B-12 status during pregnancy was associated with improved child cognitive outcomes and developmental indexes (43,45). One study from Mexico reported that inadequate maternal dietary intake of vitamin B-12 during pregnancy was associated with poorer developmental outcomes in their infants (50).…”
Section: Discussionmentioning
confidence: 99%
“…There were no differences between children in the lower vitamin B-12 and higher vitamin B-12 groups on scores on intelligence tests or visual agnosia in multivariate analyses adjusting for familial socioeconomic status and child sex, age, and anthropometric measures. The authors also reported associations between maternal plasma vitamin B-12 concentrations during pregnancy and attention in their children at 9 y of age (43). Lower maternal plasma vitamin B-12 concentrations during pregnancy were associated with a significantly lower attention span in children at 9 y of age than were higher maternal plasma vitamin B-12 concentrations (plasma vitamin B-12 <77.0 compared with >224.0 pM; mean 6 SD: 159.0 6 41.2 compared with 182.0 6 55.2 s; P < 0.05) in multivariate analyses adjusting for familial socioeconomic status and child sex, age, length, and weight (43).…”
Section: Literature Reviewmentioning
confidence: 97%
See 2 more Smart Citations
“…Data linking lower B 12 concentrations to greater adiposity, glucose intolerance and adult cognitive decline, and lower maternal B 12 status to insulin resistance and poorer cognitive function in children, come mainly from associations in observational studies (5,18,20,30,46) . However, supplementation with physiological doses of B 12 in a rural Indian population produced a marked fall in plasma homocysteine, suggesting functional benefit (47) .…”
Section: Implications Of the Dietary Findingsmentioning
confidence: 99%